Specific stabilization of DNA G-quadruplex structures with a chemically modified complementary probe. Issue 10 (15th May 2019) - Liu, Min; Liu, Yaqian; Wu, Fan; Du, Yuhao; Zhou, Xiang
Graphical abstract: Abstract: The DNA G-quadruplex is an important higher-order structure formed from guanine-rich DNA sequences. There are many molecules which can stabilize this structure. However, the selectivity of these ligands to different G-quadruplexes was not satisfactory. Herein, we designed and synthesized a chemically modified G-quadruplex probe, Razo-DNA, for the unique stabilization of the G-quadruplex. Razo-DNA consists of two fragments: The first is an organic molecular moiety which can stabilize G-quadruplex structures, and the second is a DNA molecule that is complementary with a sequence adjacent to the guanine-rich sequence of targeted DNA. Further studies showed that Razo-DNA could precisely stabilize the targeted DNA G-quadruplex structures in vitro.